Learning in the Thick of It - Darling, Marilyn; Parry, Charles; Moore, Joseph (Harvard Business Review, 2005)
After-action reviews identify past mistakes but rarely enhance future performance. Companies wanting to fully exploit this tool should look to its master: the U.S. Army’s standing enemy brigade, where soldiers learn and improve even in the midst of battle.
Section: Meeting management
Keywords: Aerospace sector; Corporate governance; Decision making and problem solving; Defense industry; Defense sector; Fabrication and manufacturing; Meeting management; Military; North America; Organizational culture; Presentation skills; Project management; Psychology; Telecom

Donors' Learning Difficulties: Results, Relationships and Responsibilities - Eyben, Rosalind (IDS Bulletin, 2005)